Green synthesis characterization and antimicrobial activity against Staphylococcus aureus of silver nanoparticles using extracts of neem, onion and tomato. Issue 30 (30th May 2019) - Chand, Kishore; Abro, M. Ishaque; Aftab, Umair; Shah, Ahmer Hussain; Lakhan, Muhammad Nazim; Cao, Dianxue; Mehdi, Ghazanfar; Ali Mohamed, Abdalla Mohamed
Abstract : The silver nanoparticles were synthesized from the neem leaves, onions, and tomato extracts, and the antibacterial activity of the particles was studied. Abstract : Recently, it has been shown that silver nanoparticles (AgNPs) exhibit great potential for different applications, including food storage, cosmetic products, electronic components, biosensor materials, cryogenics, dental materials and especially for drug-delivery activities. In this study, we synthesized AgNPs with neem extract (NE) alone and mixed plant extracts of neem, onion and tomato (NOT) as a combined reducing and stabilizing agent by a green synthesis method at different pHs. The synthesized products were characterized by ultraviolet-visible spectroscopy (UV-vis), X-ray diffraction (XRD), dynamic light scattering (DLS), atomic force microscopy (AFM), scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The antibacterial effects of the synthesized products were studied by the Kirby disk diffusion method. It was confirmed that the AgNPs work effectively as a drug material against Gram-positive bacteria Staphylococcus aureus in nutrient agar. In addition, it was seen that the reducing and stabilizing agent NOT could work effectively with six medicines with a different nature at the maximum addition of 15 μg. However, the synthesized product with NE alone only worked for four of the medicines. Therefore, it was evident that the AgNPs synthesized with NOT extract were more susceptible to the Gram-positive bacteria Staphylococcus aureus . We believe that this new route for synthesizing AgNPs with NOT extract could be more beneficial in comparison to NE alone for improved antibacterial properties in drug-delivery applications.